Emotional information-processing correlates of positive mental health in adolescence: a network analysis approach. Issue 5 (4th July 2021) - Parsons, Sam; Songco, Annabel; Booth, Charlotte; Fox, Elaine
ABSTRACT: The combined cognitive bias hypothesis proposes that emotional information-processing biases may conjointly influence mental health. Yet, little is known about the interrelationships amongst cognitive biases, particularly in adolescence. We used data from the CogBIAS longitudinal study (Booth et al., 2017), including 450 adolescents who completed measures of interpretation bias, memory bias, and a validated measure of general mental health in a typically developing population. We used a moderated network modelling approach to examine positive mental health-related moderation of the cognitive bias network. We found that mental health was directly associated with positive and negative memory biases, and positive interpretation biases, but not negative interpretation biases. Further, we observed some mental health-related moderation of the network structure. Network connectivity decreased with higher positive mental health scores. Network approaches allow us to model complex relationships amongst cognitive biases and develop novel hypotheses for future research.